Urgensi pengakuan internasional terhadap konsekuensi politik dan hukum suatu negara dari segi teori dan fungsinya - Ilmi, M. Arif Asrorul (Maliki Interdisciplinary Journal, 2024)
Recognition is one of the most important parts in international law, in fact it can be said to be a simple element, but in reality there are many complicated things contained in it. The complexity that occurs is due to the absence of clear rules and the absence of international firmness capable of forcing recognition between these countries. In this article, we will explain the theory, ways of acknowledging and withdrawing acknowledgment as well as the functions, types, and forms that exist in acknowledgment. The library method is the chosen method for compiling the writing of this article, namely in the form of collecting data in the form of books or other scientific works related to the theme of the journal written in this article.